Match analysis of discrimination skills according to the setter attack zone position in high level volleyball - Silva, M.; Lacerda, D.; Joao, P. V. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study focuses on analyzing and understanding what happens when the setter is in the attack zone (zones 4, 3 and 2), identifying the skills that best discriminate for victory or defeat. Twenty four matches (n=24) played during the Men's Senior Volleyball World Championship - Italy 2010 were taken and analyzed with Data Volley Software. For the data analysis the discriminating function was used in order to identify the discriminating variables through the canonical structuring coefficient |SC| = .30. This study revealed that the serve point, service error, excellent set, set error, attack error, excellent dig and side-out error were discriminating variables that identify the final outcome of the match (win/lose) when the setter was in the attack zone (zones 4, 3 and 2). At the same time it showed us why teams can lose. Teams without attack, side-out, service and distribution skills can hardly win games because these skills are essential for offense building and winning.